The chemical chaperone, PBA, reduces ER stress and autophagy and increases collagen IV a5 expression in cultured fibroblasts from men With X-linked alport syndrome and missense mutations - Wang, Dongmao; Mohammad, Mardhiah; Wang, Yanyan; Tan, Rachel; Murray, Lydia S.; Ricardo, Sharon; Dagher, Hayat; Agtmael, Tom van; Savige, Judy (Elsevier, 2017)
Introduction: X-linked Alport syndrome (OMIM 301050) is caused by COL4A5 missense variants in 40% of families. This study examined the effects of chemical chaperone treatment (sodium 4-phenylbutyrate) on fibroblast cell lines derived from men with missense mutations. Methods: Dermal fibroblast cultures were established from 2 affected men and 3 normals. Proliferation rates were examined, the collagen IV a5 chain localized with immunostaining, and levels of the intra- and extracellular chains quantitated with an in-house enzyme-linked immunosorbent assay. COL4A5 mRNA was measured using quantitative reverse transcriptase polymerase chain reaction. Endoplasmic reticulum (ER) size was measured on electron micrographs and after HSP47 immunostaining. Markers of ER stress (ATF6, HSPA5, DDIT3), autophagy (ATG5, BECN1, ATG7), and apoptosis (CASP3, BAD, BCL2) were also quantitated by quantitative reverse transcriptase polymerase chain reaction. Measurements were repeated after 48 hours of incubation with 10 mM sodium 4-phenylbutyrate acid. Results: Both COL4A5 missense variants were associated with reduced proliferation rates on day 6 (P 1⁄4 0.01 and P 1⁄4 0.03), ER enlargement, and increased mRNA for ER stress and autophagy (all P values < 0.05) when compared with normal. Sodium 4-phenylbutyrate treatment increased COL4A5 transcript levels (P < 0.01), and reduced ER size (P < 0.01 by EM and P < 0.001 by immunostaining), ER stress (p HSPA5 and DDIT3, all P values < 0.01) and autophagy (ATG7, P < 0.01). Extracellular collagen IV a5 chain was increased in the M1 line only (P 1⁄4 0.06). Discussion: Sodium 4-phenylbutyrate increases collagen IV a5 mRNA levels, reduces ER stress and autophagy, and possibly facilitates collagen IV a5 extracellular transport. Whether these actions delay end- stage renal failure in men with X-linked Alport syndrome and missense mutations will only be determined with clinical trials.